2006
DOI: 10.1063/1.2177382
|View full text |Cite
|
Sign up to set email alerts
|

Structural transition from L1 phase to A1 phase in FePt films caused by ion irradiation

Abstract: Structure and magnetic properties of FePt(001) graded films deposited on glass substrates Domain wall assisted magnetization switching in (111) oriented L 1 0 FePt grown on a soft magnetic metallic glass Appl. Phys. Lett. 97, 072510 (2010); 10.1063/1.3479054 Phenomenological analysis of magnetization reversal process for L 1 0 -Fe Pt ( 001 ) particulate filmsThe effect of ion irradiation ͑B + ,Cr + ,Ga + , and Nb + ͒ on the crystalline structure and magnetic properties of L1 0 ͑face-centered tetragonal structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…The direct exchange coupling type is mostly studied for the L1 0 -ordered Fe 50 Pt 50 alloy [6][7][8][9][10], where a modification of the direct exchange coupling leads to a modification of the magnetic anisotropy. Ravelosona et al [6] have shown that light ion irradiation of the initially disordered Fe 50 Pt 50 alloy can significantly enhance the degree of L1 0 -ordering without increasing the sample temperature.…”
Section: Modification Of Exchange Couplingmentioning
confidence: 99%
“…The direct exchange coupling type is mostly studied for the L1 0 -ordered Fe 50 Pt 50 alloy [6][7][8][9][10], where a modification of the direct exchange coupling leads to a modification of the magnetic anisotropy. Ravelosona et al [6] have shown that light ion irradiation of the initially disordered Fe 50 Pt 50 alloy can significantly enhance the degree of L1 0 -ordering without increasing the sample temperature.…”
Section: Modification Of Exchange Couplingmentioning
confidence: 99%
“…Finally, we propose a nanopatterning method for this material system. According to our previous results, the ordered 1 0 structures of FePtX were easily transformed to the disordered 1 structure under ion irradiation [15][16][17][18][19][20][21]. Figure 5 shows the schematics of a nanopatterning method using an FM-PM phase change due to the 1 0 -1 structural transformation caused by ion irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14], which leads to excellent thermal stability of magnetization in nanometer-size structures. After ion irradiation, the ordered 1 0 FePt films undergo transformation from the hard-FM phase (high ) to the soft-FM phase (low ) with the disordered 1 structure (fcc, = = ) [15][16][17][18][19][20]. Although the 1 0 FePt is suitable for BPM, modifying its properties using ion irradiation is difficult due to the insensitivity of magnetization with ion irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…FePt and CoPt films have been found to have a better or a worse chemical order, and thus a higher [23][24][25] or a lower magnetic anisotropy [26], after the irradiation with light ions (He + and B + ) depending on the used dose. The production of magnetic patterns on continuous magnetic films without significant modification of the surface roughness or of the film optical indices has been demonstrated by parallel irradiation through lithographically patterned stencil masks [19], but the results have also been reported by localized delivery of the damage, using FIB facilities [10,27,28].…”
Section: Fib Fabricated Magnetic Nanostructuresmentioning
confidence: 92%